Synthesis and characterization of polyvinylidene fluoride-polytetrafluoroethylene (PVDF-PTFE) membrane, functionalize with sodium carbonate for carbon dioxide separation - Siti Rabaah Binti Hamazah (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This project investigates on the synthesis and characterization of polyvinylidene fluoride-polytetrafluoroethylene membrane (PVDF-PTFE). Sodium carbonate functions as the separator for carbon dioxide. PVDF-PTFE membrane preparation was optimized by investigating the evaporation time and ethanol concentration. The results showed that two minutes of evaporation time and 15% ethanol coagulation bath for optimum PVDF-PTFE membrane properties in mechanical strength and structure. The physical characteristics of membranes were analysed using Scanning Electron Microscopy (SEM) and analytical methods while the chemical characteristics of the membrane were investigated Fourier transform infrared spectroscopy (FTIR) analysis. SEM showed that the chosen membrane had good structure of porous layer and sponge layer for impregnation process. The element analysis using Energy Dispersive Spectroscopy (EDS) discovered that analysis sodium carbonate gel contained Na, Pt, C and F whereby phosporus showed a very high concentration in the membrane. Porosity test showed that porosity percentage will increase by decreasing the ethanol concentration. FTIR analysis discovered the presence of aliphatic hydrocarbons, alkene, alkane, amine, and tertiary amine. Performance of the membrane was tested by permeation test to analyze the permeability and selectivity from the mixture of gas (carbon dioxide and nitrogen). The membrane chosen depend on the surface morphology and the suitable cross section structure. From the permeation test, carbon dioxide is more permeable and most selective.